KAJIAN POTENSI PERKEBUNAN KELAPA MELALUI HILIRISASI PENGEMBANGAN INDUSTRI VCO DIKAWASAN PEDESAAN BATU AMPAR KABUPATEN KUBU RAYA - Ramadhia, Muflihah; Sesario, Revi (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2020)
This research provides a more accurate picture of information in the possibility of developing a coconut commodity in the core bussines in rural Batu Ampar area, and to know the information about investment needs of the possibility efforts in prospective through the development of coconut as a simple industrial activity processing Virgin Coconut Oil, in the form of pre Feasibility Industry Virgin Coconut Oil (VCO) to be develop into core bussines rural Batu Ampar area. The potential opportunities for developed of downstream coconut industry in the processed product industry in the form of VCO that provides value added products to improve the welfare of people in the rural area of Batu Ampar. Minimize the risk of business failure and provide profitable business opportunities that provide benefit for the community economy and the sustainable growth in the long term. The approach in research is done with opportunity analysis, production trials and using financialanalysis.Keywords : Coconut, Industry Virgin Coconut Oil (VCO), Financial Analysis, Business Feasibility